A STUDY ON ABILITY IN USING ACADEMIC WORDS IN WRITING REPORT TEXT BY SECOND YEAR STUDENTS OF SMAN 9 PEKANBARU - Nurjamaliah Nurjamaliah '; Mahdum Mahdum '; Mangihut Nababan Mangihut Nababan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The aims of this study was to find out (1) the percentage of academic words being used in writing report text by second year students at SMAN 9 Pekanbaru and (2) the level of the academic words being used in writing report text by second year students at SMAN 9 Pekanbaru. This study is a descriptive research by using cluster model sampling to choose the sample that was 30 students of eleventh science 5 class. The analysis was based on Academic Word List (AWL) Highlighter classified into 10 levels of frequency, from the highest (level 1) to the lowest (level 10). From the 30 written texts, it was found the most academic words used is in level 7 (22 of 64 words or 34,37%) and the leasts are level 3 and level 6 (3 words of 64 or 4,68%). And based on number of students, there are 4 of 30 (13%) students that do not use any academic words in their writing. Last, based on part of speech, the most part of speech that used is verb part of speech (39 of 64 or 61,29%) and the lowest one is adverb part of speech (1 of 64 or 1,56%). It can be concluded that the students of second year of SMAN 9 Pekanbaru has been used academic words in their writing although in a low level frequency (level 7). Therefore, it is expected for teachers to more remind the students about academic words, even for the highlevel and futur researchers to conduct similar research for improving the ability of using academic words of students.Keywords : Writing, academic words, Report text